The Risk Factors Associated with Non-Alcoholic Fatty Liver Disease - Hassan Mahmood, Madiha Abbas, Mariam Azeem, Irfan Younus, Adnan Qadir, Muhammad Habib (Pakistan Journal of Medical & Health Sciences, 2023)
Background: While non-alcoholic fatty liver disease (NAFLD) is a widespread illness that affects many people in Pakistan, little is known about its epidemiology. Although a large number of individuals have NAFLD risk factors, only a tiny proportion go on to develop serious liver conditions including cirrhosis or hepatocellular carcinoma. Identification of people who are most likely to have these consequences is essential since it will allow medical personnel to spot and address risk factors early on and, eventually, stop the illness from progressing. Objective: The purpose of this research is to look at the risk factors for NAFLD at Mayo Hospital Lahore , Pakistan.We intend to learn more about the occurrence and NAFLD risk factors in this community by performing this research. Our ultimate objective is to enhance NAFLD prevention and treatment in Pakistan, which would enhance the health outcomes for those who are afflicted. Methods: From July 2022 to December 2022, a meticulous cross-sectional investigation was carried out at the esteemed Mayo Hospital in Lahore, Pakistan, to scrutinize the risk factors responsible for the onset of non-alcoholic fatty liver disease (NAFLD). The study cohort, comprising 35 participants, was selected with great care and prudence to ensure their suitability and relevance to the research question at hand. This study aimed to unravel the intricate web of risk factors associated with NAFLD, which has emerged as a global health concern. Results: The study conducted at Mayo Hospital in Lahore, Pakistan involved 35 participants who were selected for their relevance to the research question. The study participants had a mean age of 38.89±8.50 years, with the majority being females, accounting for 80% of the sample population. Moreover, a significant proportion of the participants were housewives, representing 68.6% of the sample. The majority of the participants belonged to the middle-class socioeconomic stratum (60%). The study revealed some intriguing findings, as almost half of the participants (48.6%) had diabetes mellitus (DM) and 42.9% were classified as obese. On average, the study participants had a body weight of 72.74±8.74 units and a body height of 61.37±2.67 units. These findings provide insightful information on the risk factors for NAFLD in the Pakistani community. Conclusions: Currently, non-alcoholic fatty liver disease (NAFLD) has become the most common cause of chronic liver disease in Pakistan. This alarming trend shows how important it is for doctors and governments to give this increasing menace top priority. Controlling and reducing the harmful health effects of NAFLD in Pakistan requires the implementation of specific public health interventions and preventative initiatives. Keywords: liver, diabetes, non-alcoholic fatty liver disease